Legal Protection for Victims of Harassment in a Victimological Perspective (Case Study of Harassment in Higher Education Institutions) - Yanto, Doni; Holish, Amarru Muftie; Setiawan, Hafizh Daffa (Law Research Review Quarterly, 2023)
Sexual violence is often rooted in power imbalances, and within the realm of higher education, teachers wield authority over students through suggestions, roles, and evaluations. Unfortunately, some individuals exploit this power dynamic, engaging in sexual harassment during the execution of their professional duties. According to Komnas Perempuan's data from 2017 to 2021, tertiary institutions experienced the highest frequency of sexual violence cases, with 35 incidents, followed by 16 severe cases and 15 cases in high schools. A notable incident at Sriwijaya University in late 2021, involving harassment during final assignment guidance, underscored the urgency for regulations safeguarding victims of sexual harassment. While the government has taken steps, such as the enactment of Permendikbud Number 30 of 2021 and other legal measures, to address and prevent various forms of sexual violence, this paper aims to explore the protection of victims of sexual violence on campuses, particularly within the framework of Permendikbud Number 30 of 2021. Additionally, it delves into the analysis of victim protection in cases of sexual harassment involving UNSRI lecturers from a victimology perspective.